The incident - Baehr, Nicholas E. 1924-1986; Knight, Terry 1943-2004 (Eureka entertainment ltd., 2019)
"Late one night, two young toughs hold hostage the passengers in one car of a New York subway train." [imdb.com]
Original: USA 1967
Bildformat 1.85:1
audio commentary by film critic and writer Alexandra Heller-Nicholas ; audio commentary with with director Larry Peerce and film historian Nick Redman ; post-screening Q&A with director Larry Peerce, filmed at the 2017 Wisconsin film festival [30 mins] ; original theatrical trailer
Keywords: Film